Selected Texts: A Reference Guide to the History of Iran, Volume I (To A.D. 1500). 8thed - Vatandoust, Gholam (2014)
A reference guide containing selection of the articles on the history of Iran used as an academic source in the Iranian universities after the Islamic revolution.